High inflammatory burden predicts cardiovascular events in patients with axial spondyloarthritis: a long-term follow-up study. (September 2022) - Shi, Lin-Hong; Lam, Steven H.; So, Ho; Li, Edmund K.; Li, Tena K.; Szeto, Cheuk-Chun; Tam, Lai-Shan
Background: Axial spondyloarthritis (axSpA) patients are at higher risk of cardiovascular (CV) disease (CVD) than the general population, partly due to consequences of inflammation or its treatment. But relationship between inflammation in axSpA and cardiovascular events (CVE) is unknown. Objectives: To examine whether inflammatory burden over time can predict CVE independent of baseline CV risk factors in axSpA patients. Design: A cohort analysis was performed in patients who had been recruited since January 2001. The primary outcome was a first CVE occurring between January 2001 and December 2020. Methods: Three CVD risk scores were computed at baseline. The performance of the original and modified (*1.5 multiplication factor) CV risk algorithms were assessed. Time-varying Cox proportional hazard models and Kaplan–Meier survival analysis were used to assess whether inflammatory burden (Bath ankylosing spondylitis disease activity index [BASDAI] and inflammatory markers), nonsteroidal anti-inflammatory drugs (NSAIDs) and disease modifying antirheumatic drugs (DMARDs) can predict the development of first CVE. Results: 463 patients (35 [26–45] years, male: 360 [77.8%]) were recruited. After a median follow-up of 12 (7–19) years, 61 patients (13.2%) experienced a first CVE. Traditional/modified CV risk scores underestimated CV risk. Erythrocyte sedimentation rate (ESR) ⩾ 20 mm/h was associated with a significantly higher risk of CVE during follow-up (HR: 2.07, 95%CI [1.10, 3.98], p = 0.008). Active disease as indicated by a rising BASDAI also showed positive trend towards a higher risk of developing CVE over time. After adjusting for CV risk scores in the multivariable models, high ESR level (ESR ⩾ 20 mm/h) over time remained significantly associated with a higher risk of developing CV events. Conclusion: Increased inflammatory burden as reflected by elevated ESR levels (ESR ⩾ 20) was associated with increased risk of CVE, while the use of NSAIDs and DMARDs were not.